Invasive Neurostimulation for the Treatment of Epilepsy - Omidi, Shirin Jamal; Lundstrom, Brian Nils (Seminars in Neurology, 2025)
Although electricity has been used in medicine for thousands of years, bioelectronic medicine for treating epilepsy has become increasingly common in recent years. Invasive neurostimulation centers primarily around three approaches: vagus nerve stimulation (VNS), responsive neurostimulation (RNS), and deep brain stimulation (DBS). These approaches differ by target (e.g., cranial nerve, cortex, or thalamus) and stimulation parameters (e.g., triggered stimulation or continuous stimulation). Although typically noncurative, these approaches can dramatically reduce the seizure burden and offer patients new treatment options. There remains much to be understood about optimal targets and individualized stimulation protocols. Objective markers of seizure burden and biomarkers that quickly quantify neural excitability are still needed. In the future, bioelectronic medicine could become a curative approach that remodels neural networks to reduce pathological activity.
Keywords: stimulation; epilepsy; VNS; RNS; DBS